Electrical and impedance properties of composites: Volcanic basalt rocks - Yesilkaya, S. S.; Ozdemir, Z. Guven; Canli, N. Yilmaz; Yildiz, A.; Icelli, O.; Okutan, M. (ELSEVIER SCI LTD, 2016)
In this work, volcanic basalt rocks, which were collected from different parts of Van city located in Eastern Anatolia, have been discussed in the context of impedance properties. The real and imaginary components of dielectric constants, dielectric dissipation factor, dielectric strength, AC conductivity and s frequency exponent parameter have been determined. According to AC conductivity results, it has been determined referring to s parameters' values, correlated barrier hopping (CBH) model is valid for all volcanic basalt rock samples at high frequency region. Moreover, the critical frequency that corresponds to the change of conductivity characteristic of all basalt volcanic rocks has been determined. Furthermore, due to their low conductivities Sample-1 and Sample-2 have been suggested as promising materials for electromagnetic radiation shielding applications for the high and low frequency regions, respectively. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Hybrid; Electrical properties; Chemical analysis; Powder processing; SHIELDING EFFECTIVENESS; CONDUCTIVITY; CONCRETE; DISPERSION; IMPACT; Engineering; Materials Science